Analisis Potensi Ketersediaan Tanaman Bambu dan Pemasaran Kerajinan Bambu di Desa Kayubihi Kecamatan Bangli Kabupaten Bangli - AYU RATIH PRATIWI; I NYOMAN GEDE USTRIYANA; A.A.A WULANDIRA SAWITRI DJELANTIK (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2018)
The Potential Analysis Availability Of Bamboo Plants and The Marketing ofBamboos Product at Kayubihi Village, Bangli Distric, Bangli Regency. Analysis of the potential availability of bamboo plants in Kayubihi Village, BangliSubdistrict, Bangli Regency is divided into two analyzes, namely the analysis ofpotential availability and marketing analysis. Analysis of potential availability to knowthe potency of bamboo found in Kayubihi Village while for marketing seen marketingchannel, marketing margin, and profit margin with the election of three main productsproduced by Kayubihi Village. Types of data used in this study are qualitative data andquantitative data and data sources obtained from primary data and secondary data. Datacollection methods used there are three namely Library research, field research andstudy literature. The population in this study were 50 bamboo farmers who were alsobamboo craftsmen. Data analysis was done descriptively quantitative and qualitativedescriptive. The results showed that the analysis of potential availability with five typesof bamboo plants is under 200 clumps/ha which means not yet potential. Bamboo isprocessed into handicrafts and marketed for marketing the main products are sokasi,cakes basket, and coocked rice basked. Each product has three marketing channels. Themost profit margin obtained in each marketing channel is at producer level. The shortestmarketing margin in each channel because it is directly to the consumer.